Pengaruh Kualitas Pelayanan Terhadap Kepuasan Tamu di Hotel Berbintang Kota Bandar Lampung - Muhammad Yusuf; Ujang Ujang (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the effect of service quality on guest satisfaction at star-rated hotels in Bandar Lampung City. Service quality is a critical factor that directly determines a hotel guest’s level of satisfaction and their intention to revisit. Using a quantitative approach with descriptive-associative design, this study involved 150 respondents selected through purposive sampling from guests who had stayed at three-to-five-star hotels in Bandar Lampung during the 2024–2025 period. Data were collected through structured questionnaires based on the SERVQUAL model (Parasuraman et al., 1988), encompassing five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Multiple linear regression analysis was performed to determine the simultaneous and partial effects of each dimension on guest satisfaction. The results indicate that service quality simultaneously exerts a significant positive effect on guest satisfaction (F = 28.47; p < 0.01), with a coefficient of determination (R²) of 0.74, meaning that 74% of variance in guest satisfaction is explained by service quality dimensions. Partially, assurance (beta = 0.32; p < 0.01) and empathy (beta = 0.28; p < 0.01) were the strongest predictors of guest satisfaction. These findings underscore the importance of staff competency and personalized service delivery in enhancing hotel guest satisfaction. Hotel management is recommended to invest in continuous staff training focused on interpersonal skills and service attitude.